Exploration of virtual reality as a tool for simulating leadership and teamwork situations among university students. - Navas Colon, Willian Ricardo (2024)
In the current educational context, virtual reality emerges as a revolutionary tool. By immersing students in immersive simulated environments, it facilitates deep understanding of abstract concepts and practical application of knowledge. The present study seeks to analyze the application of virtual reality as a tool to improve leadership and teamwork skills among university students through a literature review. A literature review of existing literature on the topic of virtual reality and its application in higher education was carried out, focusing specifically on studies that address the simulation of leadership and teamwork situations. Relevant research that provided insight into the benefits and challenges of VR in this context was selected and reviewed. The results of the literature review revealed a variety of studies that support the potential of virtual reality to improve the leadership and teamwork skills of university students. Virtual reality has been found to provide immersive experiences, safe environments, and immediate feedback that promote the development of these skills. However, challenges such as assessing the impact and accessibility of the technology have also been identified.